Bioinspired Micro/Nanofluidic Ion Transport Channels for Organic Cathodes in High‐Rate and Ultrastable Lithium/Sodium‐Ion Batteries. (8th November 2018) - Zhou, Gangyong; Miao, Yue‐E; Wei, Zengxi; Mo, LuLu; Lai, Feili; Wu, Yue; Ma, Jianmin; Liu, Tianxi
Abstract: Conjugated carbonyl compounds are considered as ideal substitutes for traditional inorganic electrodes in lithium/sodium ion batteries (LIBs/SIBs) due to their excellent redox reversibility and structural tunability. Here, a flexible sandwich‐structured 3, 4, 9, 10‐perylenetetracarboxylic dianhydride (PTCDA)/reduced graphene oxide (RGO)/carbon nanotube (CNT) (PTCDA/RGO/CNT) composite film with bioinspired micro/nanofluidic ion transport channels and interconnected porous conductive frameworks is designed and obtained by vacuum‐filtration and heating methods for LIB/SIB applications. The PTCDA/RGO/CNT electrode with robust mechanical deformability exhibits high diffusion coefficients of Li + /Na + and low Warburg coefficients. Thus, desirable electrochemical performances with high capacities of 131 and 126 mA h g −1 at 10 mA g −1, and ultralong cycling stability with over 99% capacity retention after 500 cycles at 200 mA g −1 are achieved for LIBs and SIBs, respectively. In particular, Li/Na‐ion full cells consisting of lithiated or sodiated electrospun carbon nanofiber anode and PTCDA/RGO/CNT‐based cathode are developed to exhibit high energy densities of 132.6 and 104.4 W h kg −1 at the power densities of 340 and 288 W kg −1 for LIBs and SIBs, respectively. The advantageous features demonstrated by constructing bioinspired micro/nanofluidic channels may provide a new pathway toward the design of next‐generation wearable energy storage devices. Abstract : Inspired by the fast permeation of ions within the protein ion channels on cell membranes, a flexible sandwich‐structured 3, 4, 9, 10‐perylenetetracarboxylic dianhydride (PTCDA)/reduced graphene oxide (RGO)/carbon nanotube (CNT) (PTCDA/RGO/CNT) film with bioinspired three‐dimensional multilayered micro/nanochannels is designed for lithium and sodium ion batteries. Because of the unique structural features, the PTCDA/RGO/CNT electrode exhibits particularly excellent lithium/sodium storage performance and cyclic stability.